An intensified training schedule in recreational male runners is associated with increases in erythropoiesis and inflammation and a net reduction in plasma hepcidin. Issue 6 (22nd October 2018) - Moretti, Diego; Mettler, Samuel; Zeder, Christophe; Lundby, Carsten; Geurts-Moetspot, Anneke; Monnard, Arnaud; Swinkels, Dorine W; Brittenham, Gary M; Zimmermann, Michael B
ABSTRACT: Background: Iron status is a determinant of physical performance, but training may induce both low-grade inflammation and erythropoiesis, exerting opposing influences on hepcidin and iron metabolism. To our knowledge, the combined effects on iron absorption and utilization during training have not been examined directly in humans. Objective: We hypothesized that 3 wk of exercise training in recreational male runners would decrease oral iron bioavailability by increasing inflammation and hepcidin concentrations. Design: In a prospective intervention, nonanemic, iron-sufficient men ( n = 10) completed a 34-d study consisting of a 16-d control phase and a 22-d exercise-training phase of 8 km running every second day. We measured oral iron absorption and erythroid iron utilization using oral 57 Fe and intravenous 58 Fe tracers administered before and during training. We measured hemoglobin mass (mHb) and total red blood cell volume (RCV) by carbon monoxide rebreathing. Iron status, interleukin-6 (IL-6), plasma hepcidin (PHep), erythropoietin (EPO), and erythroferrone were measured before, during, and after training. Results: Exercise training induced inflammation, as indicated by an increased mean ± SD IL-6 (0.87 ± 1.1 to 5.17 ± 2.2 pg/mL; P < 0.01), while also enhancing erythropoiesis, as indicated by an increase in mean EPO (0.66 ± 0.42 to 2.06 ± 1.6 IU/L), mHb (10.5 ± 1.6 to 10.8 ± 1.8 g/kg body weight), and mean RCV (30.7 ± 4.3 to 32.7 ± 4.6 mL/kg) (all P < 0.05). Training tended to increase geometric mean iron absorption by 24% ( P = 0.083), consistent with a decreased mean ± SD PHep (7.25 ± 2.14 to 5.17 ± 2.24 nM; P < 0.05). The increase in mHb and erythroid iron utilization were associated with the decrease in PHep ( P < 0.05). Compartmental modeling indicated that iron for the increase in mHb was obtained predominantly (>80%) from stores mobilization rather than from increased dietary absorption. Conclusions: In iron-sufficient men, mild intensification of exercise intensity increases both inflammation and erythropoiesis. The net effect is to decrease hepcidin concentrations and to tend to increase oral iron absorption. This trial was registered at clinicaltrials.gov as NCT01730521.